Pengaruh Pelatihan Terhadap Kinerja Guru di SMA Negeri I Adonara Barat (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research purpose to determine the effect of training on teacher performance at SMA Negeri 1 Adonara Barat. The research uses a quantitative approach with a causal descriptive research type. The population and sample used in this study were all teachers of SMA Negeri 1 Adonara Barat totaling 48 people with a census sampling technique. The data collection technique used was a questionnaire distributed to all respondents. The data analysis technique used simple linear regression analysis. The results of the study and data analysis showed that the training variable had a significant effect on teacher performance at SMA Negeri 1 Larantuka Adonara Barat as indicated by the results of the F test with a ρ value of 61,511 with a significance of (0.000 < 0.05), and partially (t test) the training variable made a positive contribution to teacher performance with a tcount value > ttable (2.543 > 1.677) with a significance level of 0.042 < 0.05. These results indicate that training has an effect on teacher performance at SMA Negeri 1 Adonara Barat.